Effect of acidified biochar on soil phosphorus availability and fertilizer use efficiency of maize (Zea mays L.) - Niaz Ahmed (Elsevier, 2021)
This study evaluated the impact of various biochars prepared from different sources and their acidified forms on soil phosphorus (P) availability and fertilizer use efficiency (FUE) of maize (Zea mays L.) crop. Plastic pots of 20 kg capacity (59 × 46 × 15 cm) were filled with 15 kg soil and seven seeds of hybrid maize (cv. Pioneer 30Y87) were sown in each pot. Various biochars and their acidified forms, including green waste biochar (GWB), acidified green waste biochar (AGWB), corncob biochar (CCB) and acidified corncob biochar (ACCB) were added in each pot t 90 g/pot before seed sowing. The control treatments were; T1 (C + 50% P), T2 (C + 75% P) and T3 (C + 100% P). The experimental treatments included T4 (CCB + 50% P), T5 (CCB + 75% P), T6 (CCB + 100% P), T7 (ACCB + 50% P), T8 (ACCB + 75% P), T9 (ACCB + 100%P), T10 (GWB + 50%P), T11 (GWB + 75%P), T12 (GWB + 100%P), T13 (AGWB + 50%P), T14 (AGWB + 75%P) and T15 (AGWB + 100%P). Results indicated that soil pH decreased (8.5 with AGWB compared to 8.76 with C), soil organic carbon (SOC) was significantly improved with all treatments. Soil electrical conductivity (EC) and cation exchange capacity (CEC) were also influenced by GWB (26 cmolckg−1) and ACCB (7.25 cmolckg−1). Bioavailability of P was highest (90 mg kg−1) with AGWB compared to control treatments. Similarly, addition of GWB and AGWB along with 50% P recorded significant improvement in plant height and fresh weight compared to control treatments. Therefore, it is suggested that among all the biochar types, AGWB is capable of improving chemical properties of the studied soil, growth, yield and nutrient uptake in maize crop compared to sole the application of P-fertilizers.